A Critical Analysis and Comparison of two Published Academic Journals in Education Field - Abdullah, Berivan M. A. (Humanities Journal of University of Zakho, 2019)
The purpose of this study is to critically analyse and evaluate two selected journal articles. The two articles are research papers in the education field; more specifically both journals are about the usage and implementation of Communicative Language Teaching. For ease of reading, each article is dealt with separately. This paper is to pinpoint their weaknesses and strengths. The two chosen papers are also critiqued from various perspectives such as methods of data collection and analysis, research layout and organization, validity and reliability of the data collected, sampling issue and ethical considerations. Although the titles are very similar, the content was different and the papers are written differently using various instruments for collecting data. This study concluded that both articles to some extend have week points such as the use of instruments and the sampling size which were a very limited size especially in article Y. The ethical issues in both articles to some extend are considered, however, in one of the articles, it is less taken into account.